Impact of HPV vaccine hesitancy on cervical cancer in Japan: a modelling study. (April 2020) - Simms, Kate T; Hanley, Sharon J B; Smith, Megan A; Keane, Adam; Canfell, Karen
Summary: Background: Funding for human papillomavirus (HPV) vaccination in Japan began in 2010 for girls aged 12–16 years, with three-dose coverage initially reaching more than 70%. On June 14, 2013, 2 months after formal inclusion in Japan's national immunisation programme, proactive recommendations for the HPV vaccine were suspended following reports of adverse events since found to be unrelated to vaccination, but which were extensively covered in the media. Vaccine coverage subsequently dropped to less than 1% and has remained this low to date. We aimed to quantify the impact of this vaccine hesitancy crisis, and the potential health gains if coverage can be restored. Methods: In this modelling study, we used the Policy1-Cervix modelling platform. We adapted the model for Japan with use of data on HPV prevalence, screening practices and coverage, and cervical cancer incidence and mortality. We evaluated the expected number of cervical cancer cases and deaths over the lifetime of cohorts born from 1994 to 2007 in the context of the vaccine hesitancy crisis. We assessed a range of recovery scenarios from 2020 onwards, including a scenario in which routine coverage is restored to 70%, with 50% catch-up coverage for the missed cohorts (aged 13–20 years in 2020). To estimate the impact of the vaccine crisis to date, we also modelled a counterfactual scenario in which 70% coverage had been maintained in 12-year-olds from 2013 onwards. Findings: The vaccine crisis from 2013 to 2019 is predicted to result in an additional 24 600–27 300 cases and 5000–5700 deaths over the lifetime of cohorts born between 1994 and 2007, compared with if coverage had remained at around 70% since 2013. However, restoration of coverage in 2020, including catch-up vaccination for missed cohorts, could prevent 14 800–16 200 of these cases and 3000–3400 of these deaths. If coverage is not restored in 2020, an additional 3400–3800 cases and 700–800 deaths will occur over the lifetime of individuals who are 12 years old in 2020 alone. If the crisis continues, 9300–10 800 preventable deaths due to cervical cancer will occur in the next 50 years (2020–69). Interpretation: The HPV vaccine crisis to date is estimated to result in around 5000 deaths from cervical cancer in Japan. Many of these deaths could still be prevented if vaccination coverage with extended catch-up can be rapidly restored. Funding: National Health and Medical Research Council Australia Centre of Research Excellence in Cervical Cancer Control, Japan Society for the Promotion of Science.